An X-Band 6-Bit Hybrid True Time Delay With Linearly-Controlled Gₘ-C All-Pass Filter in 28nm FDSOI CMOS - Soon-Hyeok Kwon; Jung-Dong Park (IEEE Access)
This paper presents a 6-bit hybrid True Time Delay (TTD) circuit designed for X-band phased array antenna systems. The circuit integrates a conventional transmission-line (T-line) based TTD structure for short delays (1.56 ps, 3.125 ps, 6.25 ps, 12.5 ps) with a Gm-C-based all-pass filter (APF) employing a thermostat method for longer delays (25 ps, 50 ps, 75 ps). Fabricated using the 28nm FD-SOI CMOS process, the proposed TTD achieves delay times up to 100 ps with a fine control step of 1.56 ps. Measurement results validate the circuit’s performance, demonstrating excellent group delay accuracy with an RMS error of less than 1.56 ps across the operating frequency range. Furthermore, all delay states maintain isolation greater than 10 dB and ensure gain variation within ±9 dB at 9 GHz. The proposed TTD circuit provides a low-power, compact solution, which makes it a promising candidate for wideband applications requiring agile beam steering while effectively mitigating the beam squint phenomenon. The implemented TTD chip occupies a compact area of 0.54 mm2 and exhibits a power consumption of up to 13.53 mW.